Pengembangan Operational Dashboard Monitoring Penerangan Jalan Umum Berbasis Webgis (Studi Kasus: Dinas Pekerjaan Umum Bina Marga Kabupaten Malang) - Achmad Joddy Chandra Alfani; Fatwa Ramdani; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The purpose of building a GIS-based road lighting monitoring dashboard prototype is to provide solutions to problems of limitations and ease in obtaining information about public street lighting and knowing whether this GIS-based public street lighting monitoring dashboard can complete and facilitate the implementation of street lighting maintenance activities carried out by the Public Service Agency of Bina Marga Malang Regency, which currently all information is still obtained manually. From the solutions provided, the development of GIS-based operational dashboard is carried out using the high-fidelity prototype method. Which results in a prototype of operational dashboard with regard to user needs. The operational street lighting monitoring dashboard can assist the service agency in carrying out monitoring and maintenance by reducing the time needed to carry out maintenance activities from 4 days to only 1 or 2 days, namely by providing information regarding public street lighting, namely the status of lights and the location of lights inside digital map form in real-time, but there is no simulation using sensors but manual Realtime simulations have been carried out using other devices instead of sensors. Prototypes that have been developed can improve the maintenance performance of street lighting by 70% because the research hypothesis has proven to have a significant effect on public road maintenance activities with a 30% significance level that is sufficiently accurate in this study.